The use of rituximab to prevent severe delayed haemolytic transfusion reaction in immunized patients with sickle cell disease. Issue 3 (18th December 2014) - Noizat‐Pirenne, F.; Habibi, A.; Mekontso‐Dessap, A.; Razazi, K.; Chadebech, P.; Mahevas, M.; Vingert, B.; Bierling, P.; Galactéros, F.; Bartolucci, P.; Michel, M.
<x xml:space="preserve">Abstract</x> Background Delayed haemolytic transfusion reaction (DHTR) is mainly caused by an immune response to transfused red blood cells (RBCs). Immunized patients have a high risk of producing antibodies in response to further transfusion. Controlling the immune response to RBCs is therefore a major goal in sickle cell disease (SCD). Study design We report an observational study of eight alloimmunized SCD patients with history of severe DHTR who were treated with rituximab before a new transfusion to prevent further immunization and DHTR. Results Five patients showed a good clinical outcome following transfusion preceded by preemptive treatment with rituximab. The remaining patients presented mild DHTR. In all patients, the results of post‐transfusion screening tests were identical to those of pretransfusion tests; no newly formed antibodies were detected. Conclusion These cases suggest that rituximab prevents at least occurrence of newly formed antibodies in high responders and minimizes the risk of severe DHTR. This study confirms that DHTR is complex in SCD and does not rely only on the classical antigens/antibodies conflict. Considering potentially serious adverse effect of rituximab, this treatment should be considered cautiously, and only when transfusion is absolutely necessary in patients with history of severe DHTR linked to immunization.